Determinants of Consumer Purchase Decisions: An Empirical Analysis of Technology, Culture, Physical Evidence, and Promotion at Coffee Shop Medan - Husni Muharram Ritonga; Roro Rian Agustin; Ruli Arika (CERED Indonesia Institute, 2025)
This research examines the influence of Technology, Culture, Physical Evidence, and Promotion on consumer Purchase Decisions at Coffee Shop Medan. The business has experienced a sales decline of approximately 30% accompanied by several operational issues, including errors in digital payment systems, unattractive store ambience, and intense promotional competition among coffee shops in Medan. A quantitative method was employed, using multiple linear regression as the primary analytical tool. Findings demonstrate that Technology and Physical Evidence have positive and significant effects on Purchase Decisions, whereas Culture and Promotion show no significant influence. Simultaneously, all variables significantly influence Purchase Decisions. The results suggest that improving technological service quality and enhancing physical ambience are strategic priorities for strengthening consumer purchase behavior.